Inoculation methods of Azospirillum brasilense in lettuce and arugula in the hydroponic system - Carlos E. da S. Oliveira; Isabela M. B. Gato; Vitoria de A. Moreira; Arshad Jalal; Thaissa J. S. S. Oliveira; Julia R. Oliveira; Guilherme C. Fernandes; Marcelo C. M. Teixeira Filho (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT: Lettuce and arugula are the most cultivated leafy vegetables in hydroponic systems in the world, and the little information about Azospirillum brasilense effects in research in this system makes it necessary to verify the best method of inoculation of these bacteria. Therefore, this study aimed to verify the beneficial effects of inoculation methods of A. brasilense on plant growth and nutrition of lettuce and arugula grown in the hydroponic system. The study was conducted in a greenhouse with 30% shading. A randomized block design with five replicates in a 4 × 2 factorial scheme was used. Four A. brasilense inoculation methods (non-inoculated, foliar application, nutrient solution, and nutrient solution + foliar application) and two leafy vegetable species - arugula and lettuce - were evaluated. All inoculation methods improved plant height, shoot fresh and dry mass, root fresh and dry mass, fresh leaf yield, leaf chlorophyll index, accumulation of nitrogen, potassium, calcium, sulfur, phosphorus, iron, manganese, and copper and reduced nitrate accumulation in shoot and root of arugula and lettuce. Inoculation via nutrient solution + foliar application of A. brasilense is the most suitable for hydroponic arugula cultivation because it provides greater fresh leaf yield. All inoculation methods increased leaf yield in hydroponic lettuce. Hydroponic arugula and lettuce plants showed greater accumulation of nutrients and plant growth with less nitrate accumulation in the shoot under inoculation with A. brasilense.